1993
DOI: 10.1002/j.1460-2075.1993.tb05687.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of a plastid envelope DNA-binding protein which may anchor plastid nucleoids.

Abstract: Chloroplast DNA (cpDNA) binds to the envelope membrane of actively dividing chloroplasts (plastids) in young pea leaves. South‐western blotting was used to identify and characterize the protein involved in the binding of cpDNA to the envelope membrane. A 130 kDa protein in the inner chloroplast (plastid) envelope membrane binds specific sequences within the cpDNA. These included a 0.41 kbp sequence located upstream of the psaAB gene, a 0.57 kbp sequence located downstream of the petA gene and a 1.2 kbp sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
107
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 41 publications
9
107
0
Order By: Relevance
“…In total, ‫03ف‬ polypeptides from 94 to 12 kD in size were detected in nucleoids. These nucleoids have been found on the thylakoid surface (Liu and Rose, 1992) and chloroplast inner envelopes (e.g., Sato et al, 1993). The histone-like proteins were found exclusively in our two-dimensional electrophoresis maps of the peripheral proteins, which Bevan et al (1998).…”
Section: Functional Role Of Lumenal and Peripheral Thylakoid Proteinsmentioning
confidence: 53%
“…In total, ‫03ف‬ polypeptides from 94 to 12 kD in size were detected in nucleoids. These nucleoids have been found on the thylakoid surface (Liu and Rose, 1992) and chloroplast inner envelopes (e.g., Sato et al, 1993). The histone-like proteins were found exclusively in our two-dimensional electrophoresis maps of the peripheral proteins, which Bevan et al (1998).…”
Section: Functional Role Of Lumenal and Peripheral Thylakoid Proteinsmentioning
confidence: 53%
“…TAC preparations from various organisms were analyzed on SDS gels, and in this way, at least 40 polypeptides associated with TAC have been detected. However, only the a-and b-subunits of the PEP (Suck et al, 1996;, a homolog of the nuclear transcription elongation factor TFIIS (da Costa e Silva et al, 2004), and few plastid DNA-bound proteins, including PEND (Sato et al, 1993), sulfite reductase (Cannon et al, 1999;Chi-Ham et al, 2002;Sekine et al, 2002), CND41 (Murakami et al, 2000), and MFP1 (Jeong et al, 2003), have been identified until now. We used different gel filtration and affinity chromatography purification steps for the isolation of TACs from mustard and Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…At least 40 other candidate proteins that do not fulfill this criterion were also identified in our preparation, and four of them have been described before as putative candidates of the TAC. This includes PEND (Sato et al, 1993), sulfite reductase (Cannon et al, 1999;Chi-Ham et al, 2002;Sekine et al, 2002), CND41 (Murakami et al, 2000), and MFP1 (Jeong et al, 2003). Some of them are clearly contamination of other plastid multiprotein complexes, such as the small subunit of ribulose bisphosphate carboxylase, PsbS (subunit S of the photosystem II), the a-subunit of carboxyltransferase, and a putative ferritin subunit (At3g11050).…”
Section: Discussionmentioning
confidence: 99%
“…A number of mt (cp) nucleoid proteins have been identified in yeast (39)(40)(41)(42), algae (43), and plants (44,45). An intriguing example of a mt nucleoid protein is Glom, which is a structural nucleoid protein that also maintains the replication and transcriptional activity of mtDNA in slime mold (46).…”
Section: Discussionmentioning
confidence: 99%